OP0185 Significant Clinical Improvement and Reduction of Severe Flares Following Administration of an IL-6 Monoclonal Antibody in Systemic Lupus Erythematosus (SLE) Subjects with High Disease Activity. (9th June 2015) - Smolen, J.; Popa, S.; Szombati, I.; Wallace, D.; Petri, M.; Lipsky, P.; Merrill, J.; Strand, V.; Healey, P.; Li, C.; Christensen, J.; Diehl, A.; et al.
Abstract : Background: PF-04236921 is a fully human monoclonal antibody (mAb) that binds to circulating IL-6 and neutralizes its activity. This may be beneficial in reducing the disease manifestations of active SLE. Objectives: To assess the efficacy, safety, and tolerability of PF-04236921 in subjects with active SLE. Methods: 183 subjects with active SLE (SLEDAI ≥6 and ≥1 BILAG 2004 A or ≥2 Bs) received 3 doses of PF-04236921 (10, 50, or 200mg) or placebo given subcutaneously every 8 wks. The primary endpoint was the proportion of SLE Responder Index 4 (SRI-4) responders at Wk 24 using a generalized linear mixed model. The BILAG-based Combined Lupus Assessment (BICLA), frequency of severe flares, and SF-36 were also evaluated. Results: The majority of subjects were female (91.8%), mean age 40.4, with musculoskeletal and mucocutaneous organ system involvement. Baseline demographics were similar across groups. At Wk 24, there were more responders in the 10mg group vs placebo for the SRI (p=0.076) and BICLA (p=0.026). Improvement in the SF-36 PCS domain was also noted for the 10mg group vs placebo (p=0.092). For the 50mg group there were no significant differences vs placebo for the SRI (p=0.528) or BICLA (p=0.1). A post-hoc subgroup analysis was completed in subjects with high baseline disease activity [SLEDAI ≥10, detectable anti-dsDNA, low complement, or prednisone >7.5 mg/day (enriched population)]. In this subgroup, a significant effect size was observed for the SRI, BICLA, and SF-36 PCS domain for the 10mg group vs placebo. There was also a significant reduction in the frequency of severe SELENA-SLEDAI Flare Index (SFI) flares for the combined 10 and 50mg groups vs placebo for both the broad (p=0.004) and enriched populations (p=0.004). Adverse events (AEs), infectious AEs, and discontinuations due to AEs were comparable across groups. The rate of SAEs was highest in the placebo and 200mg groups and the rate of serious infections was highest in the 200mg group. There were 4 deaths; 3 in 200mg [cardiorespiratory arrest, urosepsis with pulmonary embolism (PE), and disseminated tuberculosis] and 1 in 10mg (suspected PE); further dosing of 200mg was subsequently terminated. Conclusions: An efficacy signal was apparent in the broad population following administration of an IL-6 mAb notably with regard to severe flare reduction. Greater efficacy was observed across several key parameters for the 10mg group in the enriched population compared to the broad population. The safety profile with 10 and 50mg doses appeared acceptable for both the broad and enriched population; dosing with 200mg was terminated due to safety concerns. Disclosure of Interest: J. Smolen Grant/research support from: Abbvie, Janssen, MSD, Pfizer Inc, Roche, UCB, Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, GSK, Janssen, Eli-Lilly, Medimmune, MSD, Novartis-Sandoz, Novo-Nordisk, Pfizer Inc, Roche, Samsung, Sanofi-Aventis, UCB, S. Popa: None declared, I. Szombati: None declared, D. Wallace: None declared, M. Petri Consultant for: Pfizer Inc., P. Lipsky Consultant for: Pfizer Inc., J. Merrill Consultant for: Pfizer Inc., V. Strand Consultant for: Abbvie, Amgen, Anthera, Astra-Zeneca, Biogen Idec, Bristol-Myers Squibb, Genentech, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, Sanofi-Aventis, Takeda, UCB, P. Healey Employee of: Pfizer Inc., C. Li Employee of: Pfizer Inc., J. Christensen Employee of: Pfizer Inc., A. Diehl Employee of: Pfizer Inc., J. Beebe Employee of: Pfizer Inc., M. Vincent Employee of: Pfizer Inc., J. Wajdula Employee of: Pfizer Inc., S. Sridharan Employee of: Pfizer Inc.